Model požara ob prometni nesreči v bližini jedrske elektrarne - Vidmar, Peter (Strojniški vestnik, 2006)
The basic aim of this paper is to research the relevant features of the control and management of an outdoor fire event and its influence on the safety of the surrounding area. The work is based on an analytical study of the fire's origin, its development and spread. A computer program called FDS (Fire Dynamic Simulator) is used in the work to simulate the fire's behaviour.A program based on the CFD (Computational Fluid Dynamic) model usingthe LES (Large Eddie Simulation) is used to calculate the fire's development and the spread of the combustion products in the environment. The fire's source is located in the vicinity of a hazardous plant, e.g., a power or chemical plant. The article presents the brief background of the FDS computer program and the initial and boundary conditions used in the mathematical model. The output data is discussed and the validity of the results is checked. The work also presents some corrections to the physical model used and its validation by experimental data, which influences the quality of results. The obtained results were discussed and compared with the Fire Safety Analysis report included in the Probabilistic Safety Assessment of the Krsko nuclear power plant.
Keywords: varnost protipožarna; analize varnostne; modeli; koncentracija dima; območja nevarna; požari; simulacije